Striving to promote male involvement in maternal health care in rural and urban settings in Malawi - a qualitative study - Kululanga Lucy I; Sundby Johanne; Malata Address; Chirwa Ellen (BMC, 2011)
Abstract Background Understanding the strategies that health care providers employ in order to invite men to participate in maternal health care is very vital especially in today's dynamic cultural environment. Effective utilization of such strategies is dependent on uncovering the salient issues that facilitate male participation in maternal health care. This paper examines and describes the strategies that were used by different health care facilities to invite husbands to participate in maternal health care in rural and urban settings of southern Malawi. Methods The data was collected through in-depth interviews from sixteen of the twenty health care providers from five different health facilities in rural and urban settings of Malawi. The health facilities comprised two health centres, one district hospital, one mission hospital, one private hospital and one central hospital. A semi-structured interview guide was used to collect data from health care providers with the aim of understanding strategies they used to invite men to participate in maternal health care. Results Four main strategies were used to invite men to participate in maternal health care. The strategies were; health care provider initiative, partner notification, couple initiative and community mobilization. The health care provider initiative and partner notification were at health facility level, while the couple initiative was at family level and community mobilization was at village (community) level. The community mobilization had three sub-themes namely; male peer initiative, use of incentives and community sensitization. The sustainability of each strategy to significantly influence behaviour change for male participation in maternal health care is discussed. Conclusion Strategies to invite men to participate in maternal health care were at health facility, family and community levels. The couple strategy was most appropriate but was mostly used by educated and city residents. The male peer strategy was effective and sustainable at community level. There is need for creation of awareness in men so that they sustain their participation in maternal health care activities of their female partners even in the absence of incentives, coercion or invitation.